CORRELATION OF SARS-COV-2 EXPRESSION IN THE PLACENTA AND THE INCIDENCE OF PREECLAMPSIA - LUMBANRAJA , Sarma; EFFENDI, Iman Helmy; SIAHAAN , Andre M; BANCIN, Berry E P; EDIANTO, Deri; ASROEL , Edwin Martin; SUDEWO , Yudha (African Journal of Infectious Diseases (AJID), 2022)
Background: The pandemic caused by SARS-CoV-2 also caused infection in some pregnant women. Some reports say this viral infection can show symptoms of preeclampsia. Material and Methods: We analyzed 25 pregnant women with SARS-CoV-2 infection with 4 patients presenting with symptoms of preeclampsia. we performed routine blood analysis, renal function, liver function, and IHC examination to see the expression of viral proteins in the placenta. Results: we obtained 4 patients with confirmed SARS-CoV-2 infection by RT-PCR. In these 4 cases, none of the cases showed expression of the SARS-CoV-2 viral protein in the placenta, and all 4 mothers were declared dead after treatment, and 2 babies delivered out of these 4 cases died. In one case we had fetal death in pregnancy while in one case prematurity. 2 babies born to mothers with SARS-CoV-2 infection with preeclampsia were born in good condition. There were no babies infected with SARS-CoV-2 Conclusion: We conclude that SAR-CoV-2 infection in pregnant women with comorbidities can lead to a poor prognosis for both mother and baby. We cannot yet conclude whether SARS-CoV-2 infection can cause preeclampsia, but SARS-CoV-2 infection can exacerbate preeclampsia symptoms.